Corpo, feminino e subjetivação: uma análise a partir de sujeitos portadores de Lúpus Eritematoso Sistêmico - MORAIS, Jamile Luz (Universidade Federal do Pará, 2014)
This dissertation intended to investigate, starting from the psychoanalytic method, the way of subjectivities of subject bearers of Lupus Erythematosus Systemic (LES). Leaving of the psychosomatic "character" of the disease and of your predominance in the feminine sex, we investigated if it is possible a relationship to exist between the way of subjectivities of the feminine and the development of the disease. To verify this relationship, we took as reference the two attacked patients' attendance of you LES, assisted in the context of the research. Ally to that, in order to base the attendances theoretically, we leaned over in Freud's works, Lacan and followers that stopped in the study of the symptomatic manifestations of the body, as well as in the thematic involving the way of subjectivities of the feminine and it unfolding. When considering that the body conception for the psychoanalysis is going besides the biological determinism, it was possible to verify that the subject, in the attempt of reaching your satisfaction, falls back upon the body as object of obtaining of psychic and sexual pleasure, depriving the laws of the physiology and of the anatomy. The psychosomatic phenomenon and the conversion hysteria come to evidence that, in the measure in that, at the same time in that they challenge the medical knowledge, they also dispute of us, psychologists and psychoanalysts, an explanation for such manifestations corporal, causeless organic certain. In that perspective, when placing us theoretically front those manifestations, we could identify the difference between the psychosomatic phenomena and the hysterical conversion, the one which, for being linked to the symbolic registration, it becomes susceptible to decode and interpretation. The psychosomatic phenomena, on the other hand, are characterized by being of the order of the impossible of representing, for this reason, they approach of the current manifestations in the feminine way of subjectivities, that it is outside of the language of the unconscious and, therefore, of the symbolic associations.